2020
DOI: 10.3390/ijerph17238810
|View full text |Cite
|
Sign up to set email alerts
|

Level and Determinants of Adherence to COVID-19 Preventive Measures in the First Stage of the Outbreak in Uganda

Abstract: We conducted an online survey in the first two months of the Coronavirus Disease 2019 (COVID-19) epidemic in Uganda to assess the level and determinants of adherence to and satisfaction with the COVID-19 preventive measures recommended by the government. We generated Likert scales for adherence and satisfaction outcome variables and measured them with four preventive measures, including handwashing, wearing face masks, physical distancing, and coughing/sneezing hygiene. Of 1726 respondents (mean age: 36 years;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
48
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 10 publications
11
48
9
Order By: Relevance
“…Males more often indicated various reasons for not handwashing, including there is no need to do it, they do not feel like doing it, and they have no time to do it (24). Based on other research, this may be rooted in the suggestion that women are generally more willing to maintain their health when compared with men (25).…”
Section: Discussionmentioning
confidence: 99%
“…Males more often indicated various reasons for not handwashing, including there is no need to do it, they do not feel like doing it, and they have no time to do it (24). Based on other research, this may be rooted in the suggestion that women are generally more willing to maintain their health when compared with men (25).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the existence of these guidelines and the public health importance of specific preventive measures, there is limited evidence on the extent of compliance with the COVID-19 prevention guidelines [ 16 ]. Some of the previous studies on compliance with COVID-19 prevention guidelines in Uganda have been among rural market vendors [ 17 ], among the general population in rural and urban areas [ 16 ], and among high risk groups in Kampala [ 18 , 19 ]. In all these previous studies, generally poor compliance with COVID-19 guidelines was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Other mathematical models have explored the potential impact on epidemic trajectories in African countries of i) self-isolation of suspected COVID–19 cases, ii) contact tracing, and iii) “shielding” members of the most at-risk age groups (i.e., elderly people) (20,53,56). Several surveys have documented the prevalence of protective behaviors targeting β , i.e., the transmissibility of SARS-CoV-2, in African countries (32,33,54,5759). However, they have seldom investigated whether the scale on which these behaviors are implemented might have changed over time.…”
Section: Introductionmentioning
confidence: 99%